Nuevos registros de aves uruguayas - Di Giacomo, Adrián S. (1995)
New records from uruguayan birds. Between 1987-1990 I visited 12 times "Termas del Río Dayman" (13 km SE from Salto, Uruguay). I recorded 130 species and give information on 10 species.